Radiation-Induced Changes in Tumor Vessels and Microenvironment Contribute to Therapeutic Resistance in Glioblastoma - Seo, Yun-Soo; Ko, In Ok; Park, Hyejin; Jeong, Ye Ji; Park, Ji-Ae; Kim, Kwang Seok; Park, Myung-Jin; Lee, Hae-June (Frontiers in Oncology, 2019)
Glioblastoma (GBM) is a largely fatal and highly angiogenic malignancy with a median patient survival of just over 1 year with radiotherapy (RT). The effects of RT on GBM remain unclear, although increasing evidence suggests that RT-induced alterations in the brain microenvironment affect the recurrence and aggressiveness of GBM. Glioma stem cells (GSCs) in GBM are resistant to conventional therapies, including RT. This study aimed to investigate the effect of radiation on tumor growth and the GSC microenvironment in a mouse model of glioma. To evaluate the growth-inhibitory effects of ionizing radiation on GSCs, tumor volume was measured via anatomical magnetic resonance imaging (MRI) after the intracranial injection of 1 × 104 human patient-derived GSCs (83NS cells), which exhibit marked radioresistance. When a tumor mass of ~5 mm3 was detected in each animal, 10 Gy of cranial irradiation was administered. Tumor progression was observed in the orthotopic xenografted GSC tumor (primary tumor) from a detectable tumor mass (5 mm3) to a lethal tumor mass (78 mm3) in ~7 d in the non-irradiated group. In the RT group, tumor growth was halted for almost 2 weeks after administering 10 Gy cranial irradiation, with tumor growth resuming thereafter and eventually approaching a lethal mass (56 mm3) 21 d after radiation. Radiation therapy yielded good therapeutic effects, with a 2-fold increase in GSC glioma survival; however, tumor relapse after RT resulted in higher mortality for the mice with a smaller tumor volume (p = 0.029) than the non-irradiated tumor-bearing mice. Moreover, tumor regrowth after IR resulted in different phenotypes associated with glioma aggressiveness compared with the non-irradiated mice; the apparent diffusion coefficient by diffusion MRI decreased significantly (p < 0.05, 0 Gy vs. 10 Gy) alongside decreased angiogenesis, abnormal vascular dilatation, and upregulated CD34, VWF, AQP1, and AQP4 expression in the tumor. These findings demonstrate that radiation affects GSCs in GBM, potentially resulting in therapeutic resistance by changing the tumor microenvironment. Thus, the results of this study suggest potential therapeutic targets for overcoming the resistance of GBMs to RT.